Analytical Leadership Styles to Determine the Direction of an Organization - Irmayani, Irmayani; Citriadin, Yudin; Miskan, Miskan (Pascasarjana Universitas Mataram, 2025)
The purpose of this study is to describe analytical leadership style. The research method used is literature study. The results of the study indicate that the effectiveness of achieving organizational goals is highly dependent on the quality of assistance or cooperation created and developed by leaders, both individually and in groups within or outside the organization. To achieve the effectiveness of organizational goals, leadership theories and leadership styles are needed. An effective leadership style can provide motivation to work productively and achieve targets that have been designed and determined in advance. A great team comes from a great leader. One leadership style that refers to relevant data to deeply understand the direction of an organization is analytical leadership style. One leadership style that provides effectiveness is analytical leadership style. Because analytical leadership style is a leadership style that involves a data-based approach in every aspect of leadership. Leaders who use this approach focus on a deep understanding of data and matrices to determine the direction of the organization